How Tax Policies and Business Strategies Affect MSME Actors During the Covid-19 Pandemic - Darwis Lannai; Fadel Azyumardi Syahban; Nurfadila Nurfadila; St. Hartati Haeruddin; Subhan Subhan (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
The purpose of this study was to determine the effect of tax policies and business strategies on MSME actors during the pandemic in Kolaka City. This type of research includes quantitative descriptive research. The population in this study were SMEs in Kolaka District, Kolaka City. The method used in the selection of the sample is purposive sampling method and set a sample of 52 respondents based on the established criteria. The results of this study are Tax Policy has a Positive and Significant Effect on MSME Actors in the Pandemic Period in Kolaka City. The Tax Policy in question is Tax Incentives for Taxpayers affected by the 2019 Corona Virus Disease Pandemic. And the second is a Business Strategy that has a Positive and Significant Effect on MSME Actors during the pandemic in Kolaka City. The Business Strategy in question is online marketing. Based on the results of the discussion, it can be concluded that the tax policy in this case is tax intensive for MSME actors, it is felt to be very beneficial for MSME actors during the pandemic and this tax policy provides benefits for MSME actors to increase knowledge about taxation. By using a Business Strategy, online marketing is the right strategy for MSME actors to re-increase their business activities during the pandemic.